Investigating the thermal and irradiation stability of chemical vapor deposited erbium oxide tritium barrier coatings for Li breeder blanket applications - Gardner, Hazel M.; Zilahi, Gyula; Wade-Zhu, James (Frontiers in Nuclear Engineering, 2024)
Two-micron thick erbium oxide tritium barrier coatings have been prepared by aerosol injection chemical vapor deposition and subsequently irradiated with 33 MeV Au 6+ ions at fluences up to 2.1x10 16 Au/m 2 at 550 o C. Scanning electron microscopy, X-ray diffraction and transmission electron microscopy were used to investigate the coating surface morphologies, phase structures and crosssectional microstructures as a function of irradiation and thermal treatment. XRD data was also used to extract information about the evolution of lattice strain in the coating. Some of the cubic erbia transformed to the monoclinic phase in the sample that was ion irradiated at temperature, and this was accompanied by a change from columnar to a more equiaxed grain structure. All coatings were found to experience out-of-plane tensile strain, thought to originate from thermal stresses created during coating manufacture. Thermal treatment reduced microstrains present in the as-receivedasdeposited sample, whilst the cubic-to-monoclinic phase transformation reduced strain in the cubic phase but increased strain in the monoclinic phase.